2022
DOI: 10.1016/j.jtocrr.2021.100256
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Clinical Trial of Trametinib and Ponatinib in Patients With NSCLC Harboring KRAS Mutations

Abstract: Introduction Somatic KRAS mutations occur in 25% of patients with NSCLC. Treatment with MEK inhibitor monotherapy has not been successful in clinical trials to date. Compensatory activation of FGFR1 was identified as a mechanism of trametinib resistance in KRAS-mutant NSCLC, and combination therapy with trametinib and ponatinib was synergistic in in vitro and in vivo models. This study sought to evaluate this drug combination in patients with KRAS-mutant NSCLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The failure of MEKi in NSCLC is due to multiple mechanisms, including secondary MEK mutations 11 , immune escape 12 , reactivation of the MAPK pathway by RAF dimerization 13 , or compensatory induction of RAS-related pathways 14 , 15 , 16 , which inevitably leads to the development of therapy resistance and disease recurrence. These molecular discoveries have successfully promoted the clinical application of MEKi in combination with other targeted interventions 17 , 18 . However, it is difficult to restore the sensitivity of KRAS -mutant NSCLC cells to MEKi.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of MEKi in NSCLC is due to multiple mechanisms, including secondary MEK mutations 11 , immune escape 12 , reactivation of the MAPK pathway by RAF dimerization 13 , or compensatory induction of RAS-related pathways 14 , 15 , 16 , which inevitably leads to the development of therapy resistance and disease recurrence. These molecular discoveries have successfully promoted the clinical application of MEKi in combination with other targeted interventions 17 , 18 . However, it is difficult to restore the sensitivity of KRAS -mutant NSCLC cells to MEKi.…”
Section: Introductionmentioning
confidence: 99%
“…H23 cells were highly susceptible to Tra and Pon combination treatment 33 , similar as what we observed in the VQ model. However, in a phase I clinical of KRAS mutant non-small cell lung cancer patients, it was found that combination Tra/Pon treatment was associated with cardiovascular (CV) and bleeding toxicities 34 . CV side effects of this combo treatment are not unsurprising, as Pon was temporarily withdrawn by the US Food and Drug Administration in 2013 for heart failure and other CV side effects before being returned with additional safety warnings and restrictions 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, trametinib appears to inhibit the proliferation of KRAS mutant A549 cells effectively by impairing the RAF–MEK interaction 180 . However, its resistance still exists in KRAS mutant NSCLC, which is caused by compensatory activation of FGFR1 181 . As a result, MEK inhibitors are increasingly used in combination with other inhibitors to avoid drug resistance due to the feedback regulatory mechanism induced by their use alone.…”
Section: Indirect Mut‐ras Inhibition: Intervention In Downstream Path...mentioning
confidence: 99%